Non solo Roma. Torino, i Savoia e le Fiandre nei Campeggiamenti di Emanuele Tesauro (1639) - Raviola, Blythe Alice; Bianco, Luca (Incontri. Rivista europea di studi italiani, 2015)
Non solo Roma. Torino, i Savoia e le Fiandre nei Campeggiamenti di Emanuele Tesauro (1639) This essay focuses on the siege of Saint-Omer, an episode of the Thirty Years War, as seen through the eyes of several contemporaries. The first part, written by Blythe Alice Raviola, is dedicated to Emanuele Tesauro’s Sant’Omero assediato (1639). Tesauro followed prince Thomas of Savoy as court historiographer during his Flemish campaign; therefore this book should be read within the political and diplomatic context of the Savoy court. Sant’Omero assediato is considered not only as an account of the military operations, but also as a plaidoyer for Thomas’ political and military activity. The second part of the article, by Luca Bianco, establishes several connections with art historical aspects of the siege and of Tesauro’s mission. Bianco examines the subsequent frontispieces of his book and Tesauro’s possible knowledge of Karel Van Mander’s Le livre des Peintres. The final part of the article sheds light on two little-known visual representations of the siege: an artfully drawn map by Pieter Snayers and an etching by Stefano Della Bella. Whereas the first is probably produced for military purposes, Bianco proposes Tuscan Ottavio Piccolomini, Thomas’ fellow condottiero and a noteworthy collector, as the hypothetic commissioner of Della Bella’s etching, which could be considered as a visual counterpart to Tesauro’s literary account.